2023
DOI: 10.3389/fphar.2023.1269878
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways regulated by natural active ingredients in the fight against exercise fatigue-a review

Rongyue Zhao,
Ruomeng Wu,
Junjie Jin
et al.

Abstract: Exercise fatigue is a normal protective mechanism of the body. However, long-term fatigue hinders normal metabolism and exercise capacity. The generation and recovery from exercise fatigue involves alterations in multiple signaling pathways, mainly AMPK, PI3K/Akt, Nrf2/ARE, NF-κB, PINK1/Parkin, and BDNF/TrkB, as well as MAPK signaling pathways that mediate energy supply, reduction of metabolites, oxidative stress homeostasis, muscle fiber type switching, and central protective effects. In recent studies, a ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…Furthermore, in male rats, the diversity of intestinal microbiota was found to be reduced, the abundance of Helicobacter pylori and Bacteroides showed obvious changes, and the abundance of H. pylori and Bacteroides was significantly enhanced following 4 weeks of excessive swimming training (Yuan et al, 2018). An anti-fatigue mechanism related to gut microbiota can improve the host itself and its metabolites' energy metabolism processes, enhance the intestinal mucosal barrier function, and strengthen the function of the host immune system and other factors (Zhao et al, 2023). Studies have shown that Lactobacillus in the gut of endurance athletes can promote protein utilization and improve branched-chain amino acid content to maintain muscle energy homeostasis, delaying the onset of exercise fatigue (Chen et al, 2016;Jager et al, 2020).…”
Section: 5mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in male rats, the diversity of intestinal microbiota was found to be reduced, the abundance of Helicobacter pylori and Bacteroides showed obvious changes, and the abundance of H. pylori and Bacteroides was significantly enhanced following 4 weeks of excessive swimming training (Yuan et al, 2018). An anti-fatigue mechanism related to gut microbiota can improve the host itself and its metabolites' energy metabolism processes, enhance the intestinal mucosal barrier function, and strengthen the function of the host immune system and other factors (Zhao et al, 2023). Studies have shown that Lactobacillus in the gut of endurance athletes can promote protein utilization and improve branched-chain amino acid content to maintain muscle energy homeostasis, delaying the onset of exercise fatigue (Chen et al, 2016;Jager et al, 2020).…”
Section: 5mentioning
confidence: 99%
“…(De Marchi et al, 2022;Wojcik et al, 2021). The excessive release of pro-inflammatory cytokines can also enhance body fatigue (Zhao et al, 2023). Additionally, intense exercise produces large numbers of metabolites, including blood urea nitrogen (BUN) and lactic acid (LA), which can disrupt the homeostasis of the internal environment and cause fatigue (Ament & Verkerke, 2009;Fathi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation